The effect of rest breaks on time to injury – a study on work-related ladder-fall injuries in the United States - Arlinghaus, Anna; Lombardi, David A.; Courtney, Theodore K.; Christiani, David C.; Folkard, Simon; Perry, Melissa J. (Scandinavian Journal of Work, Environment & Health, 2012)
' ' OBJECTIVES ': 'Rest breaks and other work-related temporal factors, such as time spent on task, influence the accumulation of fatigue, and thus impact occupational injury risk. The aim of this study was to investigate the effect of rest breaks on “time to injury” (the time between start of work and injury) for injured workers treated in a nationally representative sample of US emergency departments. ' ' METHODS ': 'Using the National Electronic Injury Surveillance System (NEISS), we identified 629 workers who had experienced a work-related ladder-fall. Of these, 306 were interviewed by telephone using a standardized questionnaire about the circumstances surrounding the injury. Survival analyses were used to estimate time to injury, and hazard ratios (HR) for time to injury were compared between workers who reported no rest break (reference) and workers who reported rest break(s) prior to the injury (accumulated break time categorized into 0, 1–15, 16–30, and >30 minutes). Age, gender, time of work start, injury time of day, and workload were included as covariates to control for demographic, circadian, and work-related factors, respectively. ' ' RESULTS ': 'A clear dose–response relation indicated that longer accumulated break time was associated with a significantly longer time to injury when compared to workers without rest breaks [total break time 1–15 minutes: HR 0.60, 95% confidence interval (95% CI) 0.44–0.83; 16–30 minutes: HR 0.50, 95% CI 0.33–0.75; >30 minutes: HR 0.34, 95% CI 0.23–0.51], adjusted for all covariates. ' ' CONCLUSIONS ': 'The results showed that longer total rest break time allowed for a significantly prolonged time spent on task without an injury. These findings suggest that rest break design could be used as a tool to enhance fatigue management and workplace safety.
Keywords: emergency department; fall; fatigue; ladder; occupational injury; occupational safety; rest break; safety; survival analysis; temporal factor; time on task; time to injury; United States; work hour; work scheduling